Археологічні маркери південної ділянки Муравського шляху - Єльников, М.В. (Археологія і давня історія України, 2018)
Стаття присвячена реконструкції маршруту південної ділянки Муравського шляху. За аналізом писемних джерел і картографії виділені археологічні пам'ятники, що виступають маркерами цієї комунікації. Розташування городищ часів Золотої Орди на «оріхівському напрямку» змінює погляди на характер руху Муравським шляхом й ставить питання про початок його функціонування. Muravsky Shlyah from the XVI century was one of the known routes of communication in the steppe region of the Left Bank of Ukraine. This important transport strategic highway was used both for military and commercial purposes. Reconstruction of the southern section of the Muravsky Shlyah «in a large semicircle», according to the «Kniga Bolshomu Chertezhu» — the tops of the rivers from Orel to Molochnaya, exclude its passage through water crossings. Analysis of a number of written sources and cartographic material of the XVII — early XX centuries, with the indication of «mosques» — archaeological markers on the «Orekhov route», allowed to draw a conclusion about the route of this steppe way through fords. At the river crossings, on the banks of the rivers Volchy, Кonsky and Ovecy Vody, ambassadorial missions, military and travelers fix the remains of «mosques» — hillforts period of the Golden Horde. In this region the trade routes crossed, including the Great Silk Road in the XIV century, which were of great strategic importance for a long time, — before the advent of the railway. Localization of the monuments of the Golden Horde period on this communication allows you to raise the question of its occurrence at an earlier time.